2014
DOI: 10.1016/j.neuint.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of the neuronal glutamate transporter, EAAC1, results in decreased neuronal death after pilocarpine-induced status epilepticus

Abstract: Excitatory amino acid carrier 1 (EAAC1, also called EAAT3) is a Na+-dependent glutamate transporter expressed by both glutamatergic and GABAergic neurons. It provides precursors for the syntheses of glutathione and GABA and contributes to the clearance of synaptically released glutamate. Mice deleted of EAAC1 are more susceptible to neurodegeneration in models of ischemia, Parkinson’s disease, and aging. Antisense knock-down of EAAC1 causes an absence seizure-like phenotype. Additionally, EAAC1 expression incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…However, a recent study found reduced neuronal death in the CA1 region in pilocarpine-induced status epilepticus of EAAT3 KO mice (Lane et al, 2014). These data were interpreted to indicate that, under the experimental conditions used, EAAT3 reverses transport, since during a seizure ATP levels decline and the sodium driving force collapses (Streck et al, 2006; Kovac et al, 2012), leading to the protective effect of knocking out EAAT3 and implicating its role in seizure kindling.…”
Section: Eaat3 In Diseasementioning
confidence: 99%
“…However, a recent study found reduced neuronal death in the CA1 region in pilocarpine-induced status epilepticus of EAAT3 KO mice (Lane et al, 2014). These data were interpreted to indicate that, under the experimental conditions used, EAAT3 reverses transport, since during a seizure ATP levels decline and the sodium driving force collapses (Streck et al, 2006; Kovac et al, 2012), leading to the protective effect of knocking out EAAT3 and implicating its role in seizure kindling.…”
Section: Eaat3 In Diseasementioning
confidence: 99%
“…Consistent with this idea, EAAT3-null mice present with decreased neuronal GSH levels, increased indicators of neuronal oxidative stress, age-dependent neurodegeneration as well as cognitive impairment and behavioral abnormalities [ 11 , 16 , 17 ]. These mice are also more susceptible to neurodegeneration in models of ischemia, Parkinson’s disease, and aging [ 8 , 11 , 18 , 19 , 20 , 21 ]. Interestingly, it has been observed that treatment of mice with N-acetylcysteine (NAC), a membrane-permeable cysteine precursor, attenuates or prevents the biochemical and behavioral abnormalities in EAAT3-null mice [ 11 , 17 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…EAAT3, encoded by the SLC1A1 gene, ubiquitously exists in the brain and is enriched in the neurons of hippocampus and cortex [ 6 , 7 ]. Previous studies have found out that EAAT3 dysfunction may lead to neuropsychiatric diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), Huntington’s disease, epilepsy, and schizophrenia [ 8 , 9 , 10 , 11 , 12 , 13 ]. Evidence has also shown that SLC1A1 /EAAT3 overexpression could cause pathologic effects on dopaminergic neurotransmission and increase the risk of obsessive-compulsive disorder (OCD) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%